PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO FOTOGRAFI STILL LIFE MENGGUNAKAN SMARTPHONE UNTUK EKSTRAKURIKULER FOTOGRAFI MTsN 2 MAGELANG - Fatkhurrachman, Muhammad; Handoko, Aran (AKSA: Jurnal Desain Komunikasi Visual, 2025)
This study aims to: (1) Identify the development process of a Still Life photography learning video using a smartphone for the photography extracurricular program at MTsN 2 Magelang, and (2) Determine the feasibility of the Still Life photography learning video using a smartphone for the same program. The research employed the R&D (Research and Development) method with the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The feasibility of the media was assessed using a Likert scale, and data were analyzed both quantitatively and qualitatively through research instruments including questionnaires, interviews, and observations. The assessment involved experts in media, subject matter, and language, as well as 20 students participating in the photography extracurricular program at MTsN 2 Magelang. The results of the study indicate that: (1) The Still Life photography learning video using a smartphone can be developed through the ADDIE model, which includes the steps of needs and problem analysis, creation of flowcharts, scripts, storyboards, gathering of supporting media, pre-production, production, post-production, product testing, and evaluation. (2) The feasibility of the learning video was rated with an average expert score of 88.15%, categorized as “Highly Feasible” (A), and user feedback yielded an average score of 92.4%, also categorized as “Highly Feasible” (A)